Metabolit Antibakteri dari Aspergillus nidulans DSP 20, Jamur Endofit Mangrove Asosiasi Sesuvium portulacastrum - safwan safwan; Baiq Desti Isnanda Maolia; Yuli Fitriana; Abdul Rahman Wahid; Widayatul Khairi (Jurnal Insan Farmasi Indonesia, 2026)
Mangrove-associated endophytic fungi are promising producers of antibacterial secondary metabolites. This study evaluated the potential of Aspergillus nidulans DSP 20, isolated from leaves of Sesuvium portulacastrum collected from the Sekotong mangrove-associated ecosystem, as a producer of antibacterial metabolites. The isolate was obtained through surface sterilization of leaf tissue, colony purification, and morphological characterization. Metabolite production was performed by 21-day solid-state fermentation followed by ethyl acetate extraction. The metabolite profile was qualitatively analyzed using thin-layer chromatography, while antibacterial activity was tested against Staphylococcus aureus and Escherichia coli using the disc diffusion method. DSP 20 showed morphological characteristics supporting its identification as A. nidulans, produced an ethyl acetate extract with several chromatographic spots, and formed inhibition zones against both test bacteria. These findings indicate that A. nidulans DSP 20 is a potential preliminary source of antibacterial metabolites from mangrove-associated endophytic fungi.